Pemilihan Strategi Network Operations Partner Menggunakan Metoda Swot-AHP Untuk Potensi Pasar E-Bisnis Pariwisata Di Barlingmascakeb - Hidayat Muhammad Nur - AMIK BSI Purwokerto; Edi Rakhman - STMIK Nusa Mandiri Jakarta (Evolusi : Jurnal Sains dan Manajemen, 2015)
Abstract - The terms of this partnership has been known by several names, including the strategy of cooperation with the customer (customer strategic alliance), strategic partnerships with suppliers (strategic supplier alliance) and resource utilization partnership (partnership sourcing). Similarly, Network Operations Partners in other word which is the concept of e-business among modern business management and information technology. Partnership basically combines several business entities business activities, therefore it is necessary an adequate organization.It required the preparation of a good process model applied. Strategy using SWOT analysis is a method to get a strategy based on Strengths, Weakness, Opportunities and Threaths contained in the tourism industry and is then performed using the weighting method Hierarcy Analytical Process (AHP) to determine alternative decision strategies are chosen so that businesses can formulate business strategy. As a result, the priority strategies to overcome some of the activities of the tourism business entity are (1) an alternative strategy Strengths - Threaths and alternative strategy (2) Weakness - Threaths. Keywords: Election Strategy, Network Operation Partner, SWOT, AHP, e-Business Tourism